Ice Axes for Frozen Seas : A Biblical Theology of Provocation - Brueggemann, Walter (Book collections on Project MUSE., 2014)
Endlessly cunning, elusive, and playful -- the Bible consistently unsettles even as it assures. Walter Brueggemann reveals exactly how Scripture exposes the inadequacy of the assumptions and habits that shape our lives. He finds inside Israel's ancient poetry, prophecy, narrative, and legal covenants new words that create new peoples. In so doing this book provokes a theology of transformation--one that compels new social, economic, and political practices. Brueggemann's reading reveals that we are not fated to live a life of greed, anxiety, and violence, but instead can embrace a shared life of well-being grounded in an investment in the common good. Brueggemann shows the endless ways by which the Bible provokes new life for transformed peoples.